The Real Life of Mary Ann Evans : George Eliot, Her Letters and Fiction - Bodenheimer, Rosemarie, 1946- (Book collections on Project MUSE., 1994)
Bodenheimer defines the personal paradoxes that helped to shape Eliot's fictional characters and narrative style. Bodenheimer revisits pivotal episodes in Mary Ann Evans's life and career, including the "Holy War" through which she asserted her youthful religious skepticism; her decision to elope with the married writer George Henry Lewes; and her marriage with John Cross after Lewes's death. Bodenheimer also discusses the rumor campaign that led to the discovery that "George Eliot" was a woman, and she traces the trajectory of Eliot's impassioned conflict between her ambition and her womanhood.